2018
DOI: 10.1002/bin.1517
|View full text |Cite
|
Sign up to set email alerts
|

Using self‐monitoring and differential reinforcement of low rates of behavior to decrease repetitive behaviors: A case study

Abstract: We used a reversal design to evaluate the effects of a self-monitoring system and differential reinforcement of low rates of behavior on decreasing repetitive body movements in a child with autism. A trial-based functional analysis revealed that repetitive body movements were maintained by automatic reinforcement. Treatment consisted of teaching the participant to use a self-monitoring system to monitor the occurrence of repetitive body movements.A stimulus control analysis revealed the self-monitoring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Full-session DRL is defined as reinforcement contingent on the targeted behavior occurring less often than a specified frequency throughout an entire measurement period, or session (Austin & Bevan, 2011;Deitz & Repp, 1973, 1974. Researchers have demonstrated the effectiveness of fullsession DRL across a variety of response topographies (e.g., talking out, Deitz & Repp, 1973; bids for attention, Austin & Bevan, 2011;excessive compliments and physical contact, Gadaire et al, 2017;rapid eating, Wright & Vollmer, 2002), populations (e.g., age ranges; e.g., Becraft et al, 2017, Gadaire et al, 2017, Otalvaro et al, 2020abilities and disabilities, e.g., Deitz & Repp, 1973, Gadaire et al, 2017, Piper et al, 2020, environments (e.g., general education and special education; e.g., Austin & Bevin, 2011;Dietz & Repp, 1973;Dietz & Repp, 1974) and in conjunction with other interventions (e.g., self-monitoring, Looney et al, 2018;response blocking, Wright & Vollmer, 2002;group contingencies, Groves & Austin, 2017). In settings with larger staff-to-student ratios, like a classroom, full-session DRL may be easier to implement than interval or spaced-responding DRL because fewer observers are required; therefore, a full-session DRL schedule may appeal to teachers and school staff (Austin & Bevan, 2011;Becraft et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Full-session DRL is defined as reinforcement contingent on the targeted behavior occurring less often than a specified frequency throughout an entire measurement period, or session (Austin & Bevan, 2011;Deitz & Repp, 1973, 1974. Researchers have demonstrated the effectiveness of fullsession DRL across a variety of response topographies (e.g., talking out, Deitz & Repp, 1973; bids for attention, Austin & Bevan, 2011;excessive compliments and physical contact, Gadaire et al, 2017;rapid eating, Wright & Vollmer, 2002), populations (e.g., age ranges; e.g., Becraft et al, 2017, Gadaire et al, 2017, Otalvaro et al, 2020abilities and disabilities, e.g., Deitz & Repp, 1973, Gadaire et al, 2017, Piper et al, 2020, environments (e.g., general education and special education; e.g., Austin & Bevin, 2011;Dietz & Repp, 1973;Dietz & Repp, 1974) and in conjunction with other interventions (e.g., self-monitoring, Looney et al, 2018;response blocking, Wright & Vollmer, 2002;group contingencies, Groves & Austin, 2017). In settings with larger staff-to-student ratios, like a classroom, full-session DRL may be easier to implement than interval or spaced-responding DRL because fewer observers are required; therefore, a full-session DRL schedule may appeal to teachers and school staff (Austin & Bevan, 2011;Becraft et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a DRL system provides behavioral feedback to the individual without immediately removing the reinforcer, potentially providing more learning trials to target the behavior aimed for reduction. DRL schedules have been used alone or as part of a package treatment targeting various behaviors, including the reduction of requests for teacher attention (Austin & Bevan, 2011), self‐injurious behavior (Bonner & Borrero, 2018), rapid eating (Wright & Vollmer, 2002), and repetitive motor behaviors (Looney et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They saw an improvement of 96% in the reduction of talk-outs. Looney et al (2018) evaluated the effects of a self-monitoring system and a DRL on decreasing repetitive body movements in children with autism. A trial-based functional analysis revealed that automatic reinforcement maintained repetitive body movements.…”
Section: Spaced-respondingmentioning
confidence: 99%
“…For example, DRA uses an extinction component of not providing reinforcement to the target behavior. Given the positive improvements in reducing behavior with the DRL variation that targeted function-based behaviors (attention maintained, automatic), further examination of this topic is warranted (Bonner & Borrero, 2017;Looney et al, 2018;Shaw & Simms, 2009). A study might compare the treatment of attention-maintained behavior self-injurious behavior, and automatic self-injurious behaviors with these DRL variants.…”
Section: Functional Analysismentioning
confidence: 99%
See 1 more Smart Citation